Sphenoid sinus is a rare site for tumor-induced osteomalacia: A case report and literature review - Wang, Fen; He, Wentao; Ma, Delin; Xu, Weijie; Xie, Junhui; Yuan, Gang (Frontiers in Endocrinology, 2023)
Background In this paper, we present a rare case of tumor-induced osteomalacia (TIO) and a literature review of this rare disease. Methods A case of TIO of the isolated sphenoid sinus was reported. Furthermore, the clinical features of TIO in the sphenoid sinus and other sinonasal sinuses were also reviewed and summarized. Results A 35-year-old man with muscle weakness and lower back pain came to the Department of Neurology. No obvious neurological disease was found; however, magnetic resonance imaging of the extremities accidentally showed a tumor in the axilla. Bone scintigraphy showed suspicious bone metastasis. Hypophosphatemia was neglected. Interestingly, 2-deoxy-2-[fluorine-18]fluoro-d-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) detected a tumor in the axilla and another in the sphenoid sinus, but only the tumor in the sphenoid sinus had somatostatin receptor (SSTR) expression in 68-gallium 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid octreotate (Ga-68 DOTATATE) PET/CT. The sphenoid sinus tumor was proven to be a phosphaturic mesenchymal tumor (PMT), and the phosphate levels returned to normal after surgery. The literature review showed only 17 cases of TIOs that occurred in the sphenoid sinus, with an average age of 43.3 ± 13.7 years. Only three cases of TIOs in the sphenoid sinus did not invade the nasal cavity or other paranasal sinuses, which could be identified as isolated sphenoid sinus diseases. We compared the clinical features of sphenoid TIOs with those of non-sphenoid sinonasal TIOs, and it was found that the concentration of 1,25-dihydroxy vitamin D in the group with sphenoid TIOs was much higher than that in the group with non-sphenoid sinonasal TIOs. A total of 153 cases of TIOs in the sinonasal sinus were reviewed. The ethmoid sinus was found to be the major site (64.7%), followed by the nasal cavity (50.3%), maxillary sinus (19.0%), frontal sinus (16.4%), and sphenoid sinus (11.8%). There were 66 patients (43.1%) who showed tumors invading more than one sinus. Most of the tumors (69.3%) were diagnosed as PMTs by pathology, followed by hemangiopericytoma (14.3%). Immunostaining was beneficial in the differential diagnosis of these tumors; however, larger sample sizes are needed for better accuracy. Conclusion TIO in the sinonasal sinus, especially in the sphenoid sinus, is rare. Moreover, isolated sphenoid sinus disease can be easily misdiagnosed. When the clinical manifestation of osteomalacia is atypical, associating it with sphenoid sinus disease is even more difficult. Thus, TIO in the sphenoid sinus needs further exploration.